Different minds : gifted children with AD/HD, Asperger syndrome, and other learning deficits - Lovecky, Deirdre V., 1945- (Jessica Kingsley Publishers, 2004)
Through recognizing the different levels and kinds of giftedness, this book provides an insight into the challenges and benefits specific to gifted children with attention difficulties. Explaining why certain children are gifted and how giftedness is manifested, each chapter on a specific topic addresses the relevance for children with AD/HD and Asperger Syndrome. Lovecky guides parents and professionals through methods of diagnosis and advises on how best to nurture individual needs, positive behavior and relationships at home and at school. Lovecky explores concepts such as asynchrony and th.